Gegen falsche Götter und falsche Bildung : Tatian, Rede an die Griechen - Gemeinhardt, Peter, 1970-; Gemeinhardt, Peter, 1970-; Nesselrath, Heinz-Günther, 1957- (Sapere (Darmstadt, Germany), 2016)
Tatian's "Speech to the Greeks" (2nd century AD) is the vehement attack by an educated Christian against the entire Hellenic world of culture and gods and thus a forerunner of the great disputes between pagan religious traditions and Christianity in the 4th century AD The volume offers the original text, a new German translation with thorough detailed commentary as well as essays on the theological, religious and spiritual historical context of Scripture and its reception.